The Implementation of Dementia Care Mapping in a Randomized Controlled Trial in Long-Term Care: Results of a Process Evaluation. Issue 6 (September 2019) - Surr, Claire A.; Griffiths, Alys W.; Kelley, Rachael; Holloway, Ivana; Walwyn, Rebecca E. A.; Martin, Adam; McDermid, Joanne; Chenoweth, Lynn; Farrin, Amanda J.
This study explored intervention implementation within a pragmatic, cluster randomized controlled trial of Dementia Care Mapping™ (DCM) in UK care homes. DCM is a practice development tool comprised of a 5 component cycle (staff briefing, mapping observations, data analysis and reporting, staff feedback, and action planning) that supports delivery of person-centered care. Two staff from the 31 intervention care homes were trained in DCM and asked to deliver 3 cycles over a 15-month period, supported by a DCM expert during cycle 1. Implementation data were collected after each mapping cycle. There was considerable variability in DCM implementation fidelity, dose, and reach. Not all homes trained 2 mappers on schedule, and some found it difficult to retain mappers. Only 26% of homes completed more than 1 cycle. Future DCM trials in care home settings should consider additional methods to support intervention completion including intervention delivery being conducted with ongoing external support.